2011
DOI: 10.1099/mic.0.043901-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the capsular gene locus of Streptococcus pneumoniae serogroup 6

Abstract: Streptococcus pneumoniae expressing serogroup 6 capsules frequently causes pneumococcal infections and the evolutionary origins of the serogroup 6 strains have been extensively studied. However, these studies were performed when serogroup 6 had only two known members (serotypes 6A and 6B) and before the two new members (serotypes 6C and 6D) expressing wciNβ were found. We have therefore reinvestigated the evolutionary origins of serogroup 6 by examining the profiles of the capsule gene loci and the multilocus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 34 publications
5
52
2
Order By: Relevance
“…In short, this study has ensured that serotypes 6C and 6D emerged by a complicated mechanism, as shown previously (4). The cps loci of serogroup 6 isolates constitute a mosaic structure originating from diverse donors.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In short, this study has ensured that serotypes 6C and 6D emerged by a complicated mechanism, as shown previously (4). The cps loci of serogroup 6 isolates constitute a mosaic structure originating from diverse donors.…”
Section: Discussionmentioning
confidence: 84%
“…Distinct cps loci of serotypes 6A and 6B have previously been reported to be class 2 (4, 10). Our 6X group isolates are assumed to be very similar to class 2 isolates described in previous reports (4,10). The amino acid sequences of four genes of their cps loci were very similar to each other, indicating the same origin.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mutations in the cps locus can directly translate to changes in capsular PS biochemical structure and antigenicity. For example, serologically distinct capsule types can arise because of inactivation of cps genes (2,20,21), because of incorporation of foreign genes into the cps locus (22), or by cps enzyme point mutations that modify carbohydrate substrate identity or glycosidic linkages (23). Loss of function mutation in whaF correlates with the loss of an ␣Glc residue in the serogroup 20 PS repeat unit.…”
Section: Discovery Of S Pneumoniae Serotypes 20a and 20bmentioning
confidence: 99%
“…It has been postulated that serotypes 6C and 6D emerged by the replacement of wciN ␤ in the capsular loci of serotypes 6A and 6B, respectively (3,22). However, two recent papers reported that the serotypes 6C and 6D emerged just by the replacement of the wciN ␤ and wciP mutation (5,23). Bratcher et al (5) proposed that serotype 6C has been produced by introduction of a DNA fragment spanning the capsular polysaccharide synthesis (cps) locus irrespective of serotypes 6A and serotype 6D has resulted from a recombination between the cps loci of serotypes 6B and 6C.…”
mentioning
confidence: 99%